High Prevalence of Cefotaxime Resistant Bacteria in Grazing Beef Cattle: A Cross Sectional Study - Markland, Sarah; Weppelmann, Thomas A.; Ma, Zhengxin; Lee, Shinyoung; Mir, Raies A.; Teng, Lin; Ginn, Amber; Lee, Choonghee; Ukhanova, Maria; Galindo, Sebastian; Carr, Chad; DiLorenzo, Nicolas; et al. (Frontiers in Microbiology, 2019)
Although the over-use of antibiotics during food animal production is a potential driver of antimicrobial resistant microorganisms (ARMs), a high prevalence of cefotaxime resistant bacteria (CRB) has been observed in grazing animals raised without antibiotic supplementation. In this cross-sectional study, the prevalence and concentration of CRB in beef cattle on grazing farms were investigated. Fecal samples from the recto-anal junction of cattle (n = 840) and environmental samples (n = 258) were collected from 17 farms in North and Central Florida in the US, and a survey of farm characteristics, animal husbandry practices, and antibiotic usage was conducted. CRB were detected in fecal samples from 47.4% of all cattle, with the prevalence ranging from 21.1% to 87.5% on farms, and significantly higher (P < 0.001) in calves compared to adult cows (54.1 vs 41.8%). Environmental samples had a higher prevalence than fecal samples (P < 0.001), with CRB detected in 88.6% of water, 98.7% of soil, and 95.7% of forage samples. Compared to the concentration (log CFU/g) of CRB in fecal samples (2.95, 95% CI: 2.89, 3.02), the concentration of CRB was higher (P < 0.001) in soil and forage samples (5.37, 95% CI: 5.16, 5.57) and lower (P < 0.001) in water samples (1.08, 95% CI: 0.82, 1.36). Soil microbiota from farms with high prevalence of CRB clustered closer together and the proportion of Phylum Proteobacteria was higher on farms with high prevalence of CRB resistance. Large farming operations were associated with a 58% higher likelihood of CRB detection in fecal samples. Regular cleaning of drinking troughs and the addition of ionophores to feed were associated with CRB reduction in fecal samples. Taken together, the widespread of CRB into both cattle seldom treated with cephalosporin antibiotics and the surrounding environment suggests the environment is a natural source of antimicrobial resistance in beef cattle.